Handwashing Education for Students at SDN CIMANGANTEN I Due To Prevent Covid-19 - Siva Hamdani; Aan Novianti; Paula Khofifah; Sagita Apionita; Santi Nurhasanah (Fakultas Kewirausahaan Universitas Garut, 2020)
Abstract Covid-19 has been declared a pandemic that has spread to almost all countries in the world. One of the recommended precautions is washing hands with soap, because the Covid Virus can last a long time sticking to objects. Children are vulnerable to contracting Covid-19, children are individuals who are actively moving and need assistance when playing in a pandemic situation so they are not infected. This community service activity aims to increase students' knowledge and understanding of washing hands with soap to cut the spread of the virus and other diseases. The activity was carried out with live demonstrations and the distribution of educational videos on WHO's 6 steps hand washing method. The target of the activity was 30 students of SDN Cimanganten I. The analysis was carried out on the understanding questionnaire before and after education with a pair of T test assisted by SPSS software and a significance result of 0.000 was obtained which indicated that there was a significant effect on hand washing education (6 WHO steps) on the understanding of SDN Cimanganten I students. Keywords: Hand washing, Covid-19, Education. Abstrak Covid-19 telah ditetapkan sebagai pandemik yang telah menyebar hampir ke seluruh negara di dunia . Salah satu pencegahan yang direkomendasikan adalah mencuci tangan dengan sabun, karena Virus Covid dapat bertahan lama menempel pada benda. Anak-anak termasuk rentan tertular Covid-19, anak-anak merupakan individu yang aktif bergerak dan memerlukan pendampingan saat bermain di situasi pandemi supaya tidak tertular.Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan dan pemahaman siswa terhadap cuci tangan pakai sabun agar memutus penyebaran virus dan penyakit lainnya. Kegiatan dilakukan dengan demonstrasi langsung dan penyebaran video edukasi cara cuci tangan 6 langkah WHO. Sasaran kegiatan adalah siswa SDN Cimanganten I sebanyak 30 orang. Analisa dilakukan terhadap kuisioner pemahaman sebelum dan sesudah edukasi dengan pair T test yang dibantu software SPSS dan diperoleh hasil signifikansi 0,000 yang menunjukan bahwa adanya pengaruh yang bermakna edukasi mencuci tangan (6 langkah WHO) yang dilakukan terhadap pemahaman siswa SDN Cimanganten I. Kata Kunci: Cuci tangan, Covid-19, Edukasi.